Dental Health Care Needs for Elderly Population - Narottam Praharaj1 , Debasruti Naik2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The mouth is considered as the mirror of general health of every individual and concerning this in mind,poor dental health can be a menace aspect for general health trouble in the elderly population. Due toincrease in their chronic diseases in elderly patients, they are more vulnerable to oral diseases. Thus, thegeriatric population forms a distinctive group in provisions of implementation of health care. This reviewarticle discuss about the significance of dental health care needs in geriatric population.